SELF-REPORTED ORAL HEALTH AMONG ROMANIAN PATIENTS WITH LIVER TRANSPLANT: A PILOT STUDY - Adelina Lazu; Andreea Cristiana Didilescu; Laura Dan Popa; Hendrik Simon Brand; Ruxandra Sfeatcu (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study: To use a self-reported oral health (SROH) tool among patients with liver transplant (LTx), and compare the results with those from a control sample. Patients and methods: A pilot study was conducted in Bucharest, Romania, among 10 LTx patients and 10 systemically healthy control patients. A SROH questionnaire was administrated to all participants. Clinical assessments included evaluation of periodontal status. Results: SROH responses differed regarding dental care habits. The percentage of controls using dental floss was higher compared to LTx patients (p=0.07, Fisher's exact test). Total periodontitis (moderate+severe) affected 40% of LTx patients, and 30% of controls. Conclusions: The difference between the groups was mostly related to oral hygiene habits. The questionnaire may be a useful tool to better understand oral health needs of LTx patients.